Additional educational needs : inclusive approaches to teaching - Soan, Sue (Teaching assistants., 2004)
Teaching a class of learners with many different additional educational needs can be challenging to the extreme. Based on the latest national legislation and the importance of achieving 'inclusive communities' within schools, this book provides succinct and practical information on working with children with a full range of additional educational needs. This book: covers unfamiliar areas beyond the typical SEN spectrum - such as gifted and talented, bilingual learners and supporting children in careappropriate for every key stage and educational setting.